THE INFLUENCE OF STUDY HABITS AND THE ENVIRONMENT ON MATHEMATICS LEARNING ACHIEVEMENT OF CLASS X SCIENCE 2 STUDENTS AT SMA NEGERI 8 KOTA SERANG - Citra Elvina Sianturi; Jaka Wijaya Kusuma; Maulida Nur (Nindikayla Institute, 2023)
This research is motivated by student learning achievement, which is still far from expected. Student achievement is still meagre. Based on previous research, it is known that study habits and learning environments affect students' mathematics achievement. This study aims to determine whether there is an influence of study habits on learning achievement, learning environment on learning achievement and whether study habits and learning environment together affect learning achievement. This study uses a quantitative method with an ex post facto approach. With a total sample of 38 students of class X IPA 2 SMA Negeri 8 Serang City. The data collection technique in this study was distributing questionnaires for the variables of study habits and learning environment for the variable of learning achievement using test questions. The results of the t-test of study habits have a positive and significant effect on students' mathematics learning achievement. The value of tcount > ttable (3.404 > 1.688) with a significant level of 0.002 < 0.005, and the learning environment variable has no significant effect on learning achievement as evidenced by the value of tcount < ttable (0.626 < 1.688) with a significant level of 0.536 > 0.005. The results of the F test show an effect of study habits and learning environment together on students' mathematics learning achievement as evidenced by the value of fcount > ftable (6.318 > 3.27). Study habits and learning environment have a combined effect of contributing 26.5% to learning achievement. So it can be concluded that there is a significant effect of study habits on learning achievement. The learning environment variable does not have a significant effect on learning. The variables of study habits and learning environment significantly affect mathematics learning achievement, contributing to 26.5%